Performance evaluation of irrigation scheme at Dimama Angerf Abay, Awi Zone, Amhara region, Ethiopia - Yeshaneh Amsalu; Arega Mulu (Discover Water)
Abstract Performance assessment is essential to evaluate the performance of different irrigation schemes. Different irrigation schemes in Ethiopia reduced their productivity due to undefined reasons. Dimama Angerf Abay irrigation scheme is one of the irrigation schemes in Ethiopia that faced a variety of maintenance and operational issues, together with water management and sustainability issues, which drastically reduce the benefits of irrigation schemes. These performance issues are not evaluated in this specific area. Therefore, assessing the performance of this irrigation scheme is essential. Hence, the main objective of this study is to assess the performance of the existing Dimama Angerf Abay irrigation scheme using Remote sensing Portal Water Productivity (WaPOR) methods. The study was conducted during the 2022/2023 irrigation season (November to March). Primary and secondary data were collected from the field, WaPOR data source, meteorological stations, and literature. The Food and Agricultural Organization (FAO) CROPWAT package calculates crop water and irrigation demand. The WaPOR dataset and Quantum Geographic Information System (QGIS) were used to determine the actual Evapotranspiration and water productivity in the irrigation scheme during evaluation. The irrigation system was evaluated using external performance indicators (Adequacy, Equity, Uniformity, water delivery, and productivity efficiency). The result showed that the external performance indicators such as Adequacy, Equity, Uniformity, and beneficial friction rated the scheme’s performance as good, although it is poor water delivery efficiency. The overall water delivery of the scheme is fair based on the field observed data. The Remote Sensing WaPOR data analysis, on the other hand, showed that the scheme’s performance ranges from fair to good. The adequacy of the irrigation scheme was rated fair to good (75–92%), Equity range to fair (12.5–20.2%), and uniformity was categorized as good (79.8–87.5%), and beneficial friction range to fair (72–76%) based on WaPOR data source. Water productivity was ranging from 1.19 to 1.38 kg/m3. The WaPOR database is promising for evaluating irrigation system performance and water productivity. It is recommended that experts and Managers should support the farmers in adopting appropriate irrigation schedules to expand the additional command and minimize conflict.